TETRACYCLINE: A USEFUL CLASS OF ANTIBIOTICS FOR SUCCESSFUL ENDODONTICS - Jyoti, Ahlawat; Amit, Malhotra; Abhimanyu, Sharma; Chirag, Bansal (International Journal of Ayurveda and Pharma Research, 2015)
Antibiotics have been used frequently in treatment of odontogenic infections. However in endodontic diseases, the source of infection is rarely eliminated by the use of antimicrobial drugs alone. The mainstay of treating pulpal and periapical infections remains the cleaning and debridement of root canal system. Topical antibacterial agents can be used as an adjunct in the form of an irrigant or intracanal medicament during endodontic therapy. Most often employed antibiotic in endodontics is tetracycline class of drugs. Research has shown that tetracycline agents have various beneficial properties apart from bacteriostatic action, including antiresorptive activity, ability to remove smear layer from canal surface after cleaning and shaping. They also show the property of substantivity which prolongs their effect by allowing slow gradual release over time. Therefore, the present paper aims to outline the possible applications of tetracycline drugs in endodontics.